Shallow marine Paleodictyon from the Upper Ordovician Georgian Bay Formation of southern Ontario - Stanley, D.; Pickerill, R. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1993)
Two specimens, and a possible third, of the ichnotaxon Paleodictyon are documented from shallow-water marine strata of the Upper Ordovician Georgian Bay Formation of southern Ontario. Its occurrence indicates that previous suggestions of a post-Early Cambrian palaeoenvironmental retreat of Paleodictyon into deeper water require some modification. Instead, the operative migratory process, at least to the Late Ordovician and possibly even longer, was one of expansion and not of retreat.